The Triangle of Knowledge Sharing, e-Marketing Capability, Marketing Performance - Nirawati, Lia; Prayogo, Rangga Restu (University of Islam Malang, 2019)
Today's marketing activities have employed information technology to overcome the challenges of marketing sustainability in getting more resources and meeting greater expectations for building lasting relationships with customers. The ability in e-marketing represents business organizations competence in the use of the internet and other information technology to be able to facilitate effective and efficient interactions with customers. One of the marketing developments is e-Marketing capability. Information technology helps business organizations to be able to carry out online marketing capabilities. Various organizational capabilities in managing electronic-based marketing are based on knowledge sharing by business organizations to improve marketing performance. The purpose of this research is to see the extent of knowledge sharing and e-Marketing capability effect on marketing performance. This research used explanatory with a quantitative approach. The respondents are the students who have products that are marketed in business incubators. The questionnaire was given to 101 respondents with a sampling technique of purposive sampling. The results of the study show that knowledge sharing cannot influence e-Marketing capability, knowledge sharing can influence marketing performance, and e-Marketing capability cannot influence marketing performance.